Optimization of Broiler Chicken Harvest Scheduling using Integer Linear Programming: A Case Study - Setiawan, Danang; Wijaya , Hilmi Akbar (Journal of Industrial Engineering and Halal Industries, 2025)
An optimized scheduling system is essential for poultry farming to balance fluctuating market prices with fluctuating feed prices. In poultry farms, input costs account for over 90% of total expenses, with 66% allocated to feed and 25% to day-old chick purchases. This article presents an optimization model for chicken harvesting, using broiler chicken farming as a case study. A broiler chicken farm in Central Java is currently operating below optimal profitability because of a lack of a systematic harvest scheduling strategy. The Integer Linear Programming model was developed to obtain an optimal harvest schedule to maximize income with respect to operational constraints. The optimization indicates that the proposed schedule increases farm profit by 12.41% per production cycle, leading to an estimated additional yearly revenue of IDR 40,062,029. Furthermore, the sensitivity analysis indicates that market price and feed cost are the most significant factors that influence profitability, with market price fluctuations impacting profit by up to 100.17% and feeding cost changes affecting profitability by 66.10%. Minimizing the price of 5% feed can lead to an increase of 66% in profit and vice versa. This paper presents a framework of structured decision-making for poultry farms to obtain the highest possible profit and minimize loss occurrence by utilizing an optimal harvesting schedule.